2019
DOI: 10.1002/cpt.1429
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Parameters of Infliximab Influence the Rate of Relapse After De‐Escalation in Adults With Inflammatory Bowel Diseases

Abstract: This study aimed at exploring the link among individual concentrations, pharmacokinetic parameters, and the probability of relapse after de‐escalation in a real‐world prospective cohort of patients with inflammatory bowel disease (IBD) who underwent infliximab treatment de‐escalation. Ninety‐one patients were included. A time‐varying compartment model was used to estimate individual pharmacokinetic parameters and trough concentrations. A Cox model was implemented to explore the parameters influencing the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…2 As circulating levels of TNF-α can vary based on active disease-related inflammation, the amount of inflammation in patients could impact clearance of TNF-α-mediated mAbs. 2 As circulating levels of TNF-α can vary based on active disease-related inflammation, the amount of inflammation in patients could impact clearance of TNF-α-mediated mAbs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 As circulating levels of TNF-α can vary based on active disease-related inflammation, the amount of inflammation in patients could impact clearance of TNF-α-mediated mAbs. 2 As circulating levels of TNF-α can vary based on active disease-related inflammation, the amount of inflammation in patients could impact clearance of TNF-α-mediated mAbs.…”
mentioning
confidence: 99%
“…2 As circulating levels of TNF-α can vary based on active disease-related inflammation, the amount of inflammation in patients could impact clearance of TNF-α-mediated mAbs. 2 Combination therapy of infliximab with drugs with immunosuppressive effects can reduce diseaserelated inflammation and TNF-α as was suggested to be a factor in the case of patients receiving azathioprine who had a 15.1% decrease in infliximab clearance. 3 It has also been shown that C-reactive protein (CRP), a marker of inflammation, is positively correlated with clearance of infliximab.…”
mentioning
confidence: 99%
See 3 more Smart Citations